A Comparison between the Positivist and the Kuhnian Historiographies of Science - Haroon Rahman, M. Adnan (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
A Comparison between the Positivist and the Kuhnian Historiographies of Science